Front crawl and backstroke arm coordination in swimmers with down syndrome - Querido, A.; Marques-Aleixo, I.; Figueiredo, P.; Seifert, L.; Chollet, D.; Vilas-Boas, J. P.; Daly, D.; Corredeira, R.; Fernandes, R. J. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Recent studies have shown that the evaluation of arm coordination provides new information to the classic analysis (Chollet et al., 2008). Studies focusing specifically on swimmers with Down syndrome (DS) are very scarce. In that perspective, the aim of this study was to characterize the Index of Arm Coordination (IdC) in swimmers with Down syndrome. METHODS: Six international level swimmers with DS participated in this study (age: 20.2 ± 4.8 years, height: 154.3 ± 12.1 cm, weight: 58.4 ± 14.1 kg and fat mass: 16.4 ± 11.6 %). All swimmers performed 2 x 20 m swims at maximal intensity. The IdC was considered as the time gap between the propulsion of the two arms and expressed as a percentage of the duration of the complete arm stroke cycle. The level of significance was established at 5%. RESULTS: The IdC for the front crawl was -11.3% ± 5.2% and for the backstroke -13.5 ± 4.8%. For front crawl, a significant relationship was found between IdC and the relative duration of the push phase (r = 0.88), as well as with the propulsive phase (r = 0.92). An inverse relationship was found between IdC and the non propulsive phase (r = -0.92). In backstroke, there was a significant inverse relationship between IdC and velocity (r = -0.89). DISCUSSION: The international level swimmers with DS of this study presented a catch-up arm coordination mode in front crawl, which may be associated with less proficient arm coordination (Seifert et al., 2008). Trained swimmers usually change from catchup to superposition with increasing velocities. The catch-up coordination mode was also found in all swimmers for the backstroke, which is in concordance with the literature on less skilled swimmers and for skilled swimmers at low velocities (Chollet et al., 2008). This instrument can be very helpful to coaches in better understanding underwater stroke phases. The findings also emphasize the importance of augmenting the propulsive phases of the arms and, with this, diminishing the lag time of the swimmers. Technical mistakes can also be detected through the study of the arm coordination.